Controllable negative Poisson's ratio structure friction nanometer generator and preparation method thereof
Through the controllable design of the negative Poisson's ratio structure and 3D printing technology, the problems of mechanical flexibility and energy conversion efficiency of the friction nanogenerator are solved, and efficient charge transfer and structural stability are achieved, which is suitable for wearable devices and smart medical fields.
Patent Information
- Application Number
- CN202510830804.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-10-03
AI Technical Summary
Existing friction nanogenerators have shortcomings in mechanical flexibility, energy conversion efficiency and structural stability. Traditional preparation processes make it difficult to achieve precise coordinated deformation of the core-shell structure. The structural distortion problem during the material solidification process seriously restricts the reliability and service life of the device.
A controllable design of a negative Poisson's ratio structure is adopted. The negative Poisson's ratio polyurethane shell skeleton and the polytetrafluoroethylene negative friction layer are prepared by 3D printing technology. Combined with the freeze-drying process, a positive Poisson's ratio collagen aggregate foam core is formed to achieve synergistic deformation of the core-shell structure, increase the friction contact area and improve the charge transfer efficiency.
The output power and stability of the friction nanogenerator are improved, adapting to the needs of mechanical energy collection in complex environments, and suitable for fields such as wearable devices and smart medical care.
Smart Images

Figure CN120750206A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of triboelectric nanogenerators, and in particular relates to a triboelectric nanogenerator with a controllable negative Poisson's ratio structure and a preparation method thereof. Background Art
[0002] Triboelectric nanogenerators (TNGs) convert widespread mechanical vibration energy into usable electrical energy through a coupling mechanism of contact electrification and electrostatic induction. Due to their high conversion efficiency, strong environmental adaptability, and flexible structural design, TNGs have demonstrated significant application potential in wearable electronics, self-powered sensors, and the Internet of Things (IoT). In the wearable sector in particular, TNGs can directly convert the mechanical energy generated by human motion into electrical energy, providing a continuous power supply for smart devices, reducing reliance on traditional chemical batteries and promoting the development of green energy technologies.
[0003] Material system design and interface property regulation are key elements in improving the performance of triboelectric nanogenerators. Current technologies typically use a combination of materials with different electron affinities as positive and negative friction layers, such as nylon and cellulose as positively charged materials and polydimethylsiloxane and polyvinylidene fluoride as negatively charged materials. To further enhance the surface charge density, researchers generally adopt micro-nanostructure engineering strategies to increase the effective contact area by constructing nanofibers, micro-convex arrays, or biomimetic porous structures. However, the processing of such microstructures often relies on complex processes such as high-precision photolithography and ion etching, which not only results in high production costs, but also faces severe challenges in mechanical stability and large-scale preparation compatibility.
[0004] In recent years, structural innovations in negative Poisson's ratio metamaterials have provided a new direction for breakthroughs in the performance of friction nanogenerators. When the material is subjected to axial stretching, the negative Poisson's ratio lateral expansion characteristics can simultaneously increase the contact area of the friction interface, thereby significantly improving the energy capture efficiency. Although initial progress has been made in introducing the negative Poisson's ratio effect into friction nanogenerators, there are still key technical bottlenecks in practical applications: traditional preparation processes make it difficult to achieve precise coordinated deformation of the core-shell structure, and the interface bonding strength and charge transfer efficiency between the functional layers need to be improved; at the same time, structural distortion during the material solidification process causes the negative Poisson's ratio effect to attenuate, seriously restricting the reliability and service life of the device. These defects make the development of new friction nanogenerators that combine efficient energy conversion and stable mechanical response an important research direction in this field. Summary of the Invention
[0005] To overcome the shortcomings of existing triboelectric nanogenerators in terms of mechanical flexibility, energy conversion efficiency, and structural stability, the present invention provides a triboelectric nanogenerator with a controllable negative Poisson's ratio structure and its fabrication method. This generator utilizes the deformable nature of the negative Poisson's ratio structure to increase the effective contact area of the friction layer during the contact-disconnection process, thereby enhancing charge transfer and improving output power and stability.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A controllable negative Poisson's ratio triboelectric nanogenerator, characterized by comprising a shell skeleton composed of negative Poisson's ratio polyurethane, polytetrafluoroethylene as a negative friction layer, a positive friction layer composed of positive Poisson's ratio natural collagen aggregate foam, and a silver nanowire conductive electrode layer; In the core-shell structure, the polytetrafluoroethylene negative friction layer is combined with the shell skeleton through a periodic compression coating process, and the positive friction layer forms a porous foam structure inside the shell skeleton through a freeze-drying process; The negative friction layer and the positive friction layer form a core-shell structure. When external force is applied, the negative Poisson's ratio shell layer shrinks laterally, while the positive Poisson's ratio core layer expands longitudinally, thereby synergistically increasing the friction contact area and improving the mechanical energy absorption and charge separation efficiency.
[0007] Furthermore, the negative Poisson's ratio polyurethane shell skeleton is prepared by 3D printing technology, and its internal pore structure is a gradient expansion configuration composed of concave star-shaped or fractal honeycomb units.
[0008] Furthermore, the collagen aggregates are derived from any one of sheepskin, pigskin, fish skin, cowhide, cow tendon, and ostrich skin.
[0009] A controllable negative Poisson's ratio triboelectric nanogenerator and a preparation method thereof, characterized by comprising the following steps: Step 1: Using mechanical shearing and a static mixer to dually disperse thermoplastic polyurethane particles, polylactic acid particles, and nano-silica, a negative Poisson's ratio polyurethane skeleton is prepared using 3D printing technology; constructing an auxetic structure skeleton by arranging the pore gradient of concave star-shaped or fractal honeycomb units and using a micro-extrusion melt deposition process to prepare an adjustable negative Poisson's ratio polyurethane skeleton; Step 2: Cutting the negative Poisson's ratio polyurethane skeleton described in step 1 into predetermined sizes, immersing the skeleton in a silver nanowire solution and a polytetrafluoroethylene aqueous solution, respectively, and performing periodic compression and drying steps to uniformly coat the skeleton with silver nanowires and polytetrafluoroethylene to form a negative friction layer; Step 3: Immerse the negative friction layer foam skeleton described in step 2 in a prefabricated natural collagen aggregate solution, and undergo periodic compression, air drying, freezing and freeze drying steps to form a positive Poisson's ratio collagen aggregate foam core inside the skeleton, thereby forming a core-shell structure.
[0010] Further, the following steps are included: (1) Preparation of negative Poisson's ratio polyurethane skeleton: Thermoplastic polyurethane particles (Shore A hardness 80-95) and polylactic acid particles (melt index 5-10 g / 10 min) were mixed in a ratio of 3:1-5:1, 0.5%-2% nano-silica (particle size 20-50 nm) was added, and the mixture was vacuum dried at 80-100 °C for 4-6 hours; the material blending and nanoparticle dispersion were achieved through a twin-screw extruder (temperature range 160-200 °C, speed 50-80 rpm), and the shear rate was controlled at 300-500 s⁻¹ to avoid thermal degradation of polylactic acid; the wire was drawn by water cooling (diameter 0.1-0.3 mm, tolerance ±0.02 mm), and the uniformity of the wire was controlled by an online tension sensor and a laser diameter gauge in a closed loop. Auxetic structures were constructed by arranging the pores of concave star-shaped or fractal honeycomb cells (size 0.01-1 mm, wall thickness 15%-25% of the cell size) in a gradient pattern. A micro-extrusion fused deposition process (nozzle diameter 0.05-0.15 mm, layer height 0.01-0.05 mm, nozzle temperature 180-200°C, printing speed 5-15 mm / s, and a spiral progressive filling path) was used. After printing, the structure was annealed in a 50°C thermostat for 2 hours to eliminate residual stress. The structure was then ultrasonically cleaned in deionized water for 10 minutes and dried to obtain a polyurethane skeleton with a negative Poisson's ratio effect.
[0011] (2) Preparation of negative friction layer: The polyurethane foam skeleton is completely immersed in an ethanol dispersion of silver nanowires with a concentration of 5-15 mg / mL, and a periodic compression process is used (mechanical compression is applied every 5-15 minutes, and repeated 3-6 times). After compression, it is allowed to stand and soak for 30 minutes, then taken out, and then dried at 50℃~70℃ for about 2 hours; then the above foam is immersed in a 10-30% polytetrafluoroethylene aqueous solution, and the same periodic compression process is used (mechanical compression is applied every 5-15 minutes, and repeated 3-6 times). After compression, it is allowed to stand and soak for 30 minutes, then taken out, and dried in an oven at 50~100℃ for 5 hours to form a polytetrafluoroethylene coating covering the surface of the silver nanowires, constituting a negative friction layer with a negative Poisson's ratio effect.
[0012] (3) Preparation of positive friction layer: Prepare a 2~5 wt% collagen aggregate solution and stir it at 40-60℃ at a speed of 1000 r / min for 1~2 hours until it is completely dissolved. Immerse the negative friction layer foam completely in the collagen aggregate solution and use a periodic compression process (apply mechanical compression once every about 10-30 minutes, repeat 5~10 times). After compression, let it stand and soak for 30 minutes before taking it out. Place the foam adsorbed with collagen aggregate solution in a 40~60℃ air drying oven for 1~3 hours, then quickly freeze it in liquid nitrogen and transfer it to a freeze dryer for 24 hours to completely sublimate the water, thereby forming a collagen aggregate foam core with a positive Poisson's ratio within the negative Poisson's ratio shell skeleton.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention introduces 3D printing technology into the preparation of the negative Poisson's ratio structure of the friction nanogenerator. By adjusting the printing parameters, the precise matching of the pore gradient distribution and the negative Poisson's ratio structure is achieved, which solves the problem that the traditional molding / etching process cannot continuously produce complex topological structures.
[0014] (2) The controllable negative Poisson's ratio structure friction nanogenerator prepared by the present invention makes the contact interface fit more fully when subjected to force through the core-shell cooperative deformation mechanism, so that the material can achieve efficient mechanical energy absorption during the deformation process, ensuring that the electrical signal output can still be maintained under large deformation conditions, thereby optimizing the energy conversion efficiency.
[0015] (3) The programmable design of the negative Poisson's ratio structure of the controllable negative Poisson's ratio friction nanogenerator prepared by the present invention improves the deformability of the structure, enabling it to adapt to the needs of mechanical energy collection in complex environments and is suitable for wearable devices, smart medical and sports protective equipment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic diagram of the overall structure of the controllable negative Poisson's ratio triboelectric nanogenerator of the present invention; Figure 2 Output open circuit voltage for controllable negative Poisson's ratio triboelectric nanogenerator; Figure 3 This is the power density diagram of the controllable negative Poisson's ratio structure friction nanogenerator prepared by the present invention. DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings: like Figure 1 As shown, a controllable negative Poisson's ratio structure friction nanogenerator includes a shell skeleton composed of negative Poisson's ratio polyurethane foam, polytetrafluoroethylene as a negative friction layer, a positive friction layer composed of positive Poisson's ratio natural collagen aggregate foam, and silver nanowires as electrodes.
[0018] like Figure 2 As shown in the figure, the output open-circuit voltages of the controllable negative Poisson's ratio structure friction nanogenerator described in the present invention are 92 V, 120 V, 170 V, 220 V, and 280 V when the sizes are 1×1, 1.5×1.5, 2×2, 2.5×2.5, and 3×3 cm², respectively.
[0019] like Figure 3 As shown, the area of the Poisson's ratio structure friction nanogenerator of the present invention is 1×1 cm 2 The output voltage under an external force of 170 kPa is 85 V, and the effective output power is 4.2 W / m when the external resistance is 18 MΩ. 2 . Example
[0020] (1) Preparation of negative Poisson's ratio polyurethane skeleton: Thermoplastic polyurethane particles (Shore A hardness 80) and polylactic acid particles (melt index 5 g / 10 min) were mixed in a ratio of 3:1, 0.5% nano-silica (particle size 20-50 nm) was added, and the mixture was vacuum dried at 80 °C for 4 h. The materials were blended and the nanoparticles were dispersed by a twin-screw extruder (temperature range 160 °C, speed 50 rpm), and the shear rate was controlled at 300 s⁻¹ to avoid thermal degradation of polylactic acid. The wire was drawn by water cooling (diameter 0.1 mm, tolerance ±0.02 mm), and the uniformity of the wire was controlled by an online tension sensor and a laser diameter gauge in a closed loop. Auxetic structures were constructed by arranging the pores of concave star-shaped or fractal honeycomb cells (size 0.01-1 mm, wall thickness 15% of the cell size) in a gradient pattern. A micro-extrusion fused deposition process (nozzle diameter 0.05 mm, layer height 0.01 mm, nozzle temperature 180°C, printing speed 5 mm / s, and spiral progressive filling path) was used. After printing, the structure was annealed in a 50°C thermostat for 2 hours to eliminate residual stress. The structure was then ultrasonically cleaned in deionized water for 10 minutes and dried to produce a polyurethane skeleton with a negative Poisson's ratio effect.
[0021] (2) Preparation of negative friction layer: The polyurethane foam skeleton was completely immersed in an ethanol dispersion of silver nanowires with a concentration of 5 mg / mL, and a periodic compression process was used (mechanical compression was applied every 5 minutes, repeated 6 times). After compression, it was allowed to stand and soak for 30 minutes, then taken out and dried at 50°C for about 2 hours; then the above foam was immersed in a 10% polytetrafluoroethylene aqueous solution, and the same periodic compression process was used (mechanical compression was applied every 5 minutes, repeated 6 times). After compression, it was allowed to stand and soak for 30 minutes, then taken out and dried in a 50°C oven for 5 hours to form a polytetrafluoroethylene coating covering the surface of the silver nanowires, constituting a negative friction layer with a negative Poisson's ratio effect.
[0022] (3) Preparation of positive friction layer: Prepare a 2 wt% collagen aggregate solution and stir it at 1000 r / min at 40°C for 1 hour until it is completely dissolved. Immerse the negative friction layer foam completely in the collagen aggregate solution and use a periodic compression process (apply mechanical compression every 10 minutes and repeat 10 times). After compression, let it stand and soak for 30 minutes before taking it out. Place the foam adsorbed with collagen aggregate solution in a 40°C air drying oven for 1 hour, then quickly freeze it in liquid nitrogen and transfer it to a freeze dryer for 24 hours to allow the water to completely sublime, thereby forming a collagen aggregate foam core with a positive Poisson's ratio within the negative Poisson's ratio shell skeleton. Example
[0023] (1) Preparation of negative Poisson's ratio polyurethane skeleton: Thermoplastic polyurethane particles (Shore A hardness 90) and polylactic acid particles (melt index 8 g / 10 min) were mixed in a ratio of 4:1, 1% nano-silica (particle size 20-50 nm) was added, and the mixture was vacuum dried at 90 °C for 5 h. The materials were blended and the nanoparticles were dispersed by a twin-screw extruder (temperature range 180 °C, speed 65 rpm), and the shear rate was controlled at 400 s⁻¹ to avoid thermal degradation of polylactic acid. The wire was drawn by water cooling (diameter 0.2 mm, tolerance ±0.02 mm), and the uniformity of the wire was controlled by an online tension sensor and a laser diameter gauge in a closed loop. Auxetic structures were constructed by arranging the pores of concave star-shaped or fractal honeycomb cells (size 0.01-1 mm, wall thickness 20% of the cell size) in a gradient pattern. A micro-extrusion fused deposition process (nozzle diameter 0.1 mm, layer height 0.03 mm, nozzle temperature 190°C, printing speed 10 mm / s, and spiral progressive filling path) was used. After printing, the structure was annealed in a 50°C thermostat for 2 hours to eliminate residual stress. The structure was then ultrasonically cleaned in deionized water for 10 minutes and dried to produce a polyurethane skeleton with a negative Poisson's ratio.
[0024] (2) Preparation of negative friction layer: The polyurethane foam skeleton was completely immersed in an ethanol dispersion of silver nanowires with a concentration of 10 mg / mL, and a periodic compression process was used (mechanical compression was applied every 10 minutes, repeated 4 times). After compression, it was allowed to stand and soak for 30 minutes, then taken out and dried at 60°C for about 2 hours; then the above foam was immersed in a 20% polytetrafluoroethylene aqueous solution, and the same periodic compression process was used (mechanical compression was applied every 10 minutes, repeated 4 times). After compression, it was allowed to stand and soak for 30 minutes, then taken out and dried in a 70°C oven for 5 hours to form a polytetrafluoroethylene coating covering the surface of the silver nanowires, constituting a negative friction layer with a negative Poisson's ratio effect.
[0025] (3) Preparation of positive friction layer: Prepare a 4 wt% collagen aggregate solution and stir it at 50°C at a speed of 1000 r / min for 2 hours until it is completely dissolved. Immerse the negative friction layer foam completely in the collagen aggregate solution and use a periodic compression process (apply mechanical compression once every 20 minutes, repeat 7 times). After compression, let it stand and soak for 30 minutes before taking it out. Place the foam adsorbed with collagen aggregate solution in a 50°C air drying oven for 2 hours, then quickly freeze it in liquid nitrogen and transfer it to a freeze dryer for 24 hours to allow the water to completely sublime, thereby forming a collagen aggregate foam core with a positive Poisson's ratio within the negative Poisson's ratio shell skeleton. Example
[0026] (1) Preparation of negative Poisson's ratio polyurethane skeleton: Thermoplastic polyurethane particles (Shore A hardness 95) and polylactic acid particles (melt index 10 g / 10 min) were mixed in a ratio of 5:1, 2% nano-silica (particle size 20-50 nm) was added, and the mixture was vacuum dried at 100 °C for 6 h. The materials were blended and the nanoparticles were dispersed by a twin-screw extruder (temperature range 200 °C, speed 80 rpm), and the shear rate was controlled at 500 s⁻¹ to avoid thermal degradation of polylactic acid. The wire was drawn by water cooling (diameter 0.3 mm, tolerance ±0.02 mm), and the uniformity of the wire was controlled by an online tension sensor and a laser diameter gauge in a closed loop. Auxetic structures were constructed by arranging the pores of concave star-shaped or fractal honeycomb cells (size 0.01-1 mm, wall thickness 25% of the cell size) in a gradient pattern. A micro-extrusion fused deposition process (nozzle diameter 0.15 mm, layer height 0.05 mm, nozzle temperature 200°C, printing speed 15 mm / s, and spiral progressive filling path) was used. After printing, the structure was annealed in a 50°C thermostat for 2 hours to eliminate residual stress. The structure was then ultrasonically cleaned in deionized water for 10 minutes and dried to obtain a polyurethane skeleton with a negative Poisson's ratio effect.
[0027] (2) Preparation of negative friction layer: The polyurethane foam skeleton was completely immersed in an ethanol dispersion of silver nanowires with a concentration of 15 mg / mL, and a periodic compression process was used (mechanical compression was applied every 15 minutes, repeated 3 times). After compression, it was allowed to stand and soak for 30 minutes, then taken out and dried at 70°C for about 2 hours; then the above foam was immersed in a 30% polytetrafluoroethylene aqueous solution, and the same periodic compression process was used (mechanical compression was applied every 15 minutes, repeated 3 times). After compression, it was allowed to stand and soak for 30 minutes, then taken out and dried in an oven at 100°C for 5 hours to form a polytetrafluoroethylene coating covering the surface of the silver nanowires, constituting a negative friction layer with a negative Poisson's ratio effect.
[0028] (3) Preparation of positive friction layer: Prepare a 5 wt% collagen aggregate solution and stir it at 60°C at a speed of 1000 r / min for 2 hours until it is completely dissolved. Immerse the negative friction layer foam completely in the collagen aggregate solution and use a periodic compression process (apply mechanical compression once every 30 minutes, repeat 5 times). After compression, let it stand and soak for 30 minutes before taking it out. Place the foam adsorbed with collagen aggregate solution in a 60°C air drying oven for 3 hours, then quickly freeze it in liquid nitrogen and transfer it to a freeze dryer for 24 hours to allow the water to completely sublime, thereby forming a collagen aggregate foam core with a positive Poisson's ratio within the negative Poisson's ratio shell skeleton.
Claims
1. A controllable negative Poisson's ratio triboelectric nanogenerator, characterized in that: It includes a shell skeleton composed of negative Poisson's ratio polyurethane, polytetrafluoroethylene as a negative friction layer, a positive friction layer composed of positive Poisson's ratio natural collagen aggregate foam, and a silver nanowire conductive electrode layer; the negative friction layer and the positive friction layer form a core-shell structure. In the core-shell structure, the polytetrafluoroethylene negative friction layer is combined with the shell skeleton through a periodic compression coating process, and the positive friction layer forms a porous foam structure inside the shell skeleton through a freeze-drying process.
2. The controllable negative Poisson's ratio triboelectric nanogenerator according to claim 1, characterized in that: The negative Poisson's ratio polyurethane shell skeleton is prepared by 3D printing technology, and its internal pore structure is a gradient tensile expansion configuration composed of concave star-shaped or fractal honeycomb units.
3. The controllable negative Poisson's ratio triboelectric nanogenerator according to claim 1, characterized in that: The natural collagen aggregates are derived from any one of sheepskin, pigskin, fish skin, cowhide, cow tendon and ostrich skin.
4. A method for preparing a controllable negative Poisson's ratio triboelectric nanogenerator, characterized in that: The following steps are involved: Step 1: Using mechanical shearing and a static mixer to dually disperse thermoplastic polyurethane particles, polylactic acid particles, and nano-silica, a negative Poisson's ratio polyurethane skeleton is prepared using 3D printing technology; constructing an auxetic structure skeleton by arranging the pore gradient of concave star-shaped or fractal honeycomb units and using a micro-extrusion melt deposition process to prepare an adjustable negative Poisson's ratio polyurethane skeleton; Step 2: Cutting the negative Poisson's ratio polyurethane skeleton described in step 1 into predetermined sizes, immersing the skeleton in a silver nanowire solution and a polytetrafluoroethylene aqueous solution, respectively, and performing periodic compression and drying steps to uniformly coat the skeleton with silver nanowires and polytetrafluoroethylene to form a negative friction layer; Step 3: Immerse the negative friction layer foam skeleton described in step 2 in a prefabricated natural collagen aggregate solution, and undergo periodic compression, air drying, freezing and freeze drying steps to form a positive Poisson's ratio collagen aggregate foam core inside the skeleton, thereby forming a core-shell structure.
5. The method for preparing a controllable negative Poisson's ratio triboelectric nanogenerator according to claim 4, characterized in that: The following steps are involved: (1) Preparation of negative Poisson's ratio polyurethane skeleton: Thermoplastic polyurethane particles with a Shore A hardness of 80-95 and polylactic acid particles with a melt index of 5-10 g / 10 min were mixed in a ratio of 3:1-5:1, and 0.5%-2% nano-silicon dioxide with a particle size of 20-50 nm was added. The mixture was vacuum dried at 80-100 °C for 4-6 hours. The material blending and nanoparticle dispersion were achieved by a twin-screw extruder with a temperature range of 160-200 °C and a rotation speed of 50-80 rpm. The shear rate was controlled at 300-500 s⁻¹ to avoid thermal degradation of polylactic acid. The wire was drawn by water cooling (the diameter of the wire was 0.1-0.3 mm, with a tolerance of ±0.02 mm). The uniformity of the wire was controlled by an online tension sensor and a laser diameter gauge. The wire was formed by a concave star-shaped or fractal honeycomb unit (size 0.01-1 The auxetic structure was constructed by arranging pores with a gradient of pores (mm, with a wall thickness accounting for 15%-25% of the unit size). A micro-extrusion fused deposition process was used (nozzle diameter 0.05-0.15 mm, layer height 0.01-0.05 mm, nozzle temperature 180-200°C, printing speed 5-15 mm / s, and spiral progressive filling path). After printing, the structure was annealed in a 50°C constant temperature oven for 2 hours to eliminate residual stress. It was then ultrasonically cleaned with deionized water for 10 minutes and dried to obtain a polyurethane skeleton with a negative Poisson's ratio effect. (2) Preparation of negative friction layer: The polyurethane foam skeleton is completely immersed in a silver nanowire ethanol dispersion with a concentration of 5-15 mg / mL, and a periodic compression process is used (mechanical compression is applied every 5-15 minutes, and repeated 3-6 times). After compression, it is allowed to stand and soak for 30 minutes, then taken out, and then dried at 50℃~70℃ for about 2 hours; then the above foam is immersed in a 10-30% polytetrafluoroethylene aqueous solution, and the same periodic compression process is used (mechanical compression is applied every 5-15 minutes, and repeated 3-6 times). After compression, it is allowed to stand and soak for 30 minutes, then taken out, and dried in an oven at 50~100℃ for 5 hours to form a polytetrafluoroethylene coating covering the surface of the silver nanowires, constituting a negative friction layer with a negative Poisson's ratio effect; (3) Preparation of positive friction layer: Prepare a 2~5 wt% collagen aggregate solution and stir it at 40-60℃ at a speed of 1000 r / min for 1~2 hours until it is completely dissolved. Immerse the negative friction layer foam completely in the collagen aggregate solution and use a periodic compression process (apply mechanical compression once every about 10-30 minutes, repeat 5~10 times). After compression, let it stand and soak for 30 minutes before taking it out. Place the foam adsorbed with collagen aggregate solution in a 40~60℃ air drying oven for 1~3 hours, then quickly freeze it in liquid nitrogen and transfer it to a freeze dryer for 24 hours to completely sublimate the water, thereby forming a collagen aggregate foam core with a positive Poisson's ratio within the negative Poisson's ratio shell skeleton.